The Influence of Consumer Perception and Consumer Experience on Purchasing Decisions Through Purchase Intention as a Mediating Variable on Pond's Skincare Products in Palangka Raya City - Mahrai Mahrai; Lelo Sintani; Vivy Kristinae; Meitiana Meitiana (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of consumer perception and consumer experience on purchasing decisions for Pond’s skincare products through purchase intention as a mediating variable among consumers in Palangk a Raya City. This research employed a quantitative approach, with data collected through an online questionnaire distributed via Google Forms to 100 users of Pond’s skincare products in Palangka Raya City. The sample was determined using purposive sampling based on specific criteria and obtained through a snowball sampling approach. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results indicate that consumer perception and consumer experience have a positive and significant effect on purchase intention. In addition, consumer experience and purchase intention have a positive and significant effect on purchasing decisions. However, consumer perception does not have a significant direct effect on purchasing decisions. The findings also reveal that purchase intention mediates the influence of consumer perception and consumer experience on purchasing decisions. These findings suggest that purchasing decisions for Pond’s skincare products can be enhanced through strengthening positive consumer perceptions, improving consumer experience, and developing marketing strategies that effectively increase consumers’ purchase intention.